Mesoporous carbon materials: synthesis methods, properties, and advanced applications - Wei, Zhou; Yanfei, Zhi; Jiao, Wang (Frontiers in Materials, 2025)
Mesoporous carbon materials have great potential in energy storage, catalysis and adsorption separation due to their unique pore size distribution, high specific surface area and excellent stability. This review discusses the synthesis methods of mesoporous carbon materials. The comparative analysis emphasizes the advantages and limitations of different preparation methods, providing a basis for the targeted design of mesoporous carbon materials. The properties of mesoporous carbon (high specific surface area, electrochemical, thermal stability, etc.) are introduced in detail, and the relationship between the physicochemical properties of mesoporous carbon and its electrochemical and adsorption properties is discussed, and the contribution of structural regulation to performance improvement is clarified. In addition, the practical applications of mesoporous carbon materials in supercapacitors, lithium-ion batteries, adsorption and catalysis are discussed. Challenges such as stability, cost-effectiveness and scalability are pointed out, and future research prospects in functional modification, precise structural design and environmentally sustainable synthesis are envisioned.